West : - Sherman, Dennis (McGraw-Hill, 2012)
WEST illustrates the significance of economic, political, social and cultural interactions that shaped Western Civilization while asking students to analyze events and themes in order to build a greater understanding of the past and its influence and impact on the present. With WEST, students are no longer simply reading a static page. They are interacting and engaging in a visual and hands-on learning experience. As students experience the history of Western Civilization, WEST builds the critical analysis skills that will student success in this history course and beyond.